Repeated Clozapine Increases the Level of Serotonin 5-HT1AR Heterodimerization with 5-HT2A or Dopamine D2 Receptors in the Mouse Cortex - Szlachta, Marta; Kuśmider, Maciej; Pabian, Paulina; Solich, Joanna; Kolasa, Magdalena; Żurawek, Dariusz; Dziedzicka-Wasylewska, Marta; Faron-Górecka, Agata (Frontiers in Molecular Neuroscience, 2018)
G-protein–coupled receptor (GPCR) heterodimers are new targets for the treatment of schizophrenia. Dopamine D2 receptors and serotonin 5-HT1A and 5-HT2A receptors play an important role in neurotransmission and have been implicated in many human psychiatric disorders, including schizophrenia. Therefore, in this study, we investigated whether antipsychotic drugs (clozapine and haloperidol) affected the formation of heterodimers of D2–5-HT1A receptors as well as 5-HT1A–5-HT2A receptors. Proximity ligation assay (PLA) was used to accurately visualize, for the first time, GPCR heterodimers both at in vitro and ex vivo levels. In line with our previous behavioral studies, we used ketamine to induce cognitive deficits in mice. Our study confirmed the co-localization of D2/5-HT1A and 5-HT1A/5-HT2A receptors in the mouse cortex. Low-dose clozapine (0.3 mg/kg) administered repeatedly, but not clozapine at 1 mg/kg, increased the level of D2–5-HT1A and 5-HT1A–5-HT2A heterodimers in the mouse prefrontal and frontal cortex. On the other hand, haloperidol decreased the level of GPCR heterodimers. Ketamine affected the formation of 5-HT1A–5-HT2A, but not D2–5-HT1A, heterodimers.